The impact of supporting the pricing policy to improve the production of wheat in Iraq since 2008 through 2014 - الدجيلي جعفر (Journal of Economics and Administrative Sciences, 2016)
Abstract Despite the fact of the importance and effectiveness of supporting the pricing policy for agriculture sector in Iraq, but this policy has stopped in supporting those agriculture production needs, and it was confined to support the final product only, and supporting the strategic corps exclusively after the U.S. Invasion in 2003, but after 2008 the state has returned to support some of this policy activities through providing financial loans through the agricultural initiative campaign, with trillions of iraqi dinars without any use, also providing support to some of the agricultural production needs such as fertilizers , tractors and agricultural combines, in addition supporting the pricing policy for the final product of wheat. Despite the increase of prices to buy wheat, but the impact of wheat production pricing was fragile, this is not because of the pricing but due to the huge increase in the production cost caused by the limited and weak support of government for the production requirements, and It was limited to fertilizers, tractors and agriculture combines. Also the support was stopped for the improved seeds and pesticides. Another factor is the huge increase in petroleum products pricing, in which can be used in most of the agriculture operations through Diesel generators for irrigation, tractors and combine harvesters. Pulse the increase in transportation fees, manpower and lack of government support comparing it to the huge increase that happened in the pricing for those agriculture products. Furthermore the remarkable lack in financial and technological aspects for the Iraqi farmer. Facing the monopolization of international companies for the agriculture products in which led to not export those products. So this research is to highlight the impact of pricing policy on the production of wheat in Iraq, and this research conclude that this weakness is because of the high increase in the prices of the production requirements, furthermore this research conclude to focus more on supporting the pricing for production products more than supporting the prices of the final product